Helppppp meeeeeeee :(

Question

Helppppp meeeeeeee 🙁
helppppp-meeeeeeee

in progress 0
Kiệt Gia 8 tháng 2020-11-02T05:40:58+00:00 2 Answers 53 views 0

Answers ( )

  1. $\begin{array}{l}a)\,\,5(x+3y) – 15(x+3y)\\ = 5(x+3y) -3.5(x+3y)\\ = 5(x+3y)(1 -3)\\ = 5(x+3y).2\\ = 10(x+3y)\\ b)\,\,2y^2(x+1)+ 4y(x+1)\\ =y.2y(x+1) + 2.2y(x+1)\\ = 2y(x+1)(y + 2)\\ c)\,\,2x(y – 1) + 4y(y-1)\\ = x.2(y – 1) + 2y.2(y-1)\\ = 2(y-1)(x + 2y)\\ d)\,\,8xy(x-y) – 6x(y – x)\\ = 4y.2x(x-y) + 3.2x(x- y)\\ = 2x(x-y)(4y + 3)\\ e)\,\,3(x-y) – 5x(y – x)\\ = 3(x-y) + 5x(x – y)\\ = (x-y)(3 +5x)\\ f)\,\,5x^2(x-2y) -15x(x – 2y)\\ = x.5x(x-2y) – 3.5x(x-2y)\\ = 5x(x-2y)(x- 3)\\ g)\,\,xy(x-y) – 2x + 2y\\ =xy(x-y) – 2(x-y)\\ = (x-y)(xy – 2)\\ h)\,\,(y-x)^3 – y(x-y)^2+ x(x-y)\\ = (y-x)^3 – y(y-x)^2 – x(y -x)\\ = (y-x)[(y-x)^2 – y(y-x) – x]\\ = (y-x)(y^2 – 2xy + x^2 – y^2 + xy – x)\\ = (y-x)(x^2 – xy – x)\\ = x(y-x)(x – y – 1) \end{array}$

     

  2. Mình trình bày trong hình!
    helppppp-meeeeeeee

Leave an answer